Association of Adverse Effects following COVID-19 Immunization with Previously COVID-19 Infected and Non- Infected Health Care Professionals - Bansal, Prerna; Koirala, Pallavi; Shrestha, Ayasha; Upadhyay, Hari Prasad; Khadka, Kamal; Phuyal, Ranjeeta (Journal of College of Medical Sciences-Nepal, 2022)
Introduction: The immunogenicity of COVID-19 disease and variability among adverse effects following COVID-19 vaccine in previously infected and non-infected individuals is not clearly understood. So, this study aims to assess the association of adverse effects of COVID-19 vaccine with previously infected and non-infected individuals. Methods: A case-control study was conducted at College of Medical Sciences, Bharatpur, Chitwan, Nepal from July 2021 to February 2022 among 324 health care professionals who had received two doses of COVID-19 vaccine. Cases included those who developed any adverse effects following COVID-19 immunization and controls included those who did not develop any adverse effects. Exposure was presence and non-exposure was absence of previous COVID-19 infection. The data collected was analyzed in SPSS version 17 software in terms of frequency, percentage, mean, standard deviation, chi-square, exposure rates and odds ratio. Results: Mild adverse effects like fever, myalgia, headache and pain in injection site were observed following both first dose (46.9%) and second dose (6.17%) of vaccine. The exposure rate was more in cases (23.45%) than in controls (11.11%). Odds ratio was 2.452 (95 % CI, 1.332 to 4.512, p<0.05) which is statistically significant. Conclusions: The risk of developing adverse effects following COVID-19 immunization was 2.452 times more in health care professionals who were previously infected with COVID-19 as compared to those who were not infected. Thus, there is a significant association of adverse effects following COVID-19 immunization with previous COVID-19 infection. Keywords: adverse effects; following immunization; association; case-control study; COVID-19 vaccines; health care professionals